Surface Trafficking of APP and BACE in Live Cells - Bauereiß, Anna; Welzel, Oliver; Jung, Jasmin; Grosse-Holz, Simon; Lelental, Natalia; Lewczuk, Piotr; Wenzel, Eva M.; Kornhuber, Johannes; Groemer, Teja W. (Traffic, 2015)
Amyloid-? (A?)-peptide, the major constituent of the plaques that develop during Alzheimer's disease, is generated via the cleavage of A? precursor protein (APP) by ?-site APP-cleaving enzyme (BACE). Using live-cell imaging of APP and BACE labeled with pH-sensitive proteins, we could detect the release events of APP and BACE and their distinct kinetics. We provide kinetic evidence for the cleavage of APP by ?-secretase on the cellular surface after exocytosis. Furthermore, simultaneous dual-color evanescent field illumination revealed that the two proteins are trafficked to the surface in separate compartments. Perturbing the membrane lipid composition resulted in a reduced frequency of exocytosis and affected BACE more strongly than APP. We propose that surface fusion frequency is a key factor regulating the aggregation of APP and BACE in the same membrane compartment and that this process can be modulated via pharmacological intervention.
EVALuna2:23697